Defining functional interactions between human B cells and invariant natural killer T cells form health donors and patients wiht chronic lymphocytic leukaemia - Ghnewa, Yasmeen G. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
Invariant natural killer T (iNKT) cells are a minor population of innate T cells that express semi-invariant T cell receptors that recognise glycolipid antigens (Ag) presented by CD1d. Upon activation, iNKT cells kill target cells, release cytokines that activate and regulate cellular and antibody-mediated immune responses, and promote maturation of dendritic cells into antigen presenting cells. Studies in mice and humans have shown that iNKT cells mediate immunity against tumours, and clinical trials targeting iNKT cells for the treatment of cancer are ongoing. Human B cells express CD1d and have recently been shown to stimulate iNKT cells, and iNKT cells can reciprocally provide help for antibody (Ab) production by B cells. However, iNKT cells include functionally distinct subsets based on expression of CD4 and CDS. In the present study, we investigated whether CD4+, CD8+, and DN iNKT cell subsets can differentially promote B cell differentiation, antibody production, as well as cytokine production in vitro. We optimised methods for the generation of CD4+, CD8+, and DN iNKT cell lines, and investigated the roles B cells have in activating iNKT cells through the presentation of various glycolipid antigens. In view of the well-documented roles that iNKT cells play in anti-tumour immunity and in cognate interactions with B cells, we investigated the role and treatment potential of iNKT cells in chronic lymphocytic leukaemia (CLL), a human B cell malignant neoplastic disease.
Keywords: Immunology, Ph.D.; PhD Trinity College Dublin, 2016